Peningkatan Penguasaan Kosakata Bahasa Jepang dengan Menggunakan Media Teka-Teki Silang - Stovia, Anggita; Firmansyah, Dian Bayu (Universitas Negeri Semarang, 2020)
Vocabulary mastery is one of the most important in learning Japanese. Lack of mastery of vocabulary will make students look less active when teaching and learning activities take place. The purpose of this study is to determine the effectiveness of the crossword puzzle in increasing the mastery of Japanese vocabulary. This research is an experimental study with a Posstest-Only Control Group Design model. The data generated in this study are quantitative data obtained form the results of the post test in class A as an experimental class and class B as a control class. The results of data analysis showed that the level of mastery of vocabulary in the experimental class using crossword puzzles, was higher than the control class using conventional media in the form of lecture activities using textbooks. In addition, The atmosphere of the learning by using crossword media is more interesting and fun. This is confirmed by the average results of the vocabulary test scores in the experimental class at 85.87, while in the control class at 74.8.